Subjective regulation in pedagogical activity: a comparative analysis of the control of behavior of teachers of comprehensive and special schools - M.V. Fedotova (Психолого-педагогические исследования, 2025)
Context and relevance. The article examines the problem of subjective regulation of pedagogical activity. All teachers have responsible work and operate under conditions of limited resources. However, working with children with disabilities may impose additional requirements on special education teachers, which may affect the subjective regulation of their activity. Objective. The purpose of the article is to analyze behavior control among teachers working with children with mental disabilities and teachers teaching children with typical development. Methods and materials. Based on the system-subject approach of E.A. Sergienko, a comparative analysis of the control of the behavior of teachers in general education (N = 41, M = 32,2; SD = 8,1) and special education teachers (N = 41, M = 37; SD = 12) was conducted. The total sample size was 82 respondents. At the first stage, the level of control over teachers' behavior was analyzed using the "Behavior Control" questionnaire (E.A. Sergienko, G.A. Vilenskaya, I.I. Vetrova, 2021). Results. Analysis using the Mann-Whitney U-test showed that general education teachers have a higher level of behavior control compared to special education teachers. Conclusions. At the second stage, 20 in-depth interviews were conducted, the content analysis of which allows us to draw conclusions about the conditionality of the severity of the level of behavior control by subjective adaptation strategies in the professional and life environment.